Schinus terebinthifolius raddi (Aroeira) and Orbignya phalerata mart. (Babassu) effect in cecorrahphy healing in rats - Scheibe,Christian Lamar (2016)
ABSTRACT PURPOSE: To evaluate the effect of Schinus terebinthifolius Raddi (aroeira) and Orbignya phalerata Mart. (babassu) in the healing process of cecorrhaphy in rats. METHODS : Fifty four rats were used, distributed into three groups randomly: aroeira, babassu and control, which were divided into three subgroups (six animals) according to the time of the deaths (7, 14, 21 days). All underwent the same surgical procedure, cecotomy and cecorrhaphy. The animals in group aroeira and babassu received daily dose of 100 mg/kg of hydroalcoholic extract and 50 mg/kg of aquous extract respectively, by gavage. The control group received only saline solution. The parameters evaluated were: macroscopic changes, ,resistance test to air insufflations and histological changes. RESULTS : All animals showed good healing without infection. All groups presented adhesions between cecum and neighboring organs. The resistance test insufflating of atmospheric air showed progressive increase of pressure according to the days in the aroeira group, and decrease in babassu group, without significant difference. Microscopy showed significant difference in the polymorphonuclear, hyperemia, angiogenesis, fibroblast proliferation and collagen histological variables in the 14th day. CONCLUSION : Hydroalcoholic extract of aroeira and the aqueous extract of babassu favored the healing process in cecorrhaphy in rats.